Analysis of caecal mucosal inflammation and immune modulation during Anoplocephala perfoliata infection of horses. (18th October 2019) - Lawson, April L.; Pittaway, Charles E.; Sparrow, Richard M.; Balkwill, Emily C.; Coles, Gerald C.; Tilley, Alice; Wilson, A. Douglas
Abstract: Anoplocephala perfoliata is the commonest equine tapeworm, the adult parasites are attached in groups close to the ileocaecal valve causing marked inflammatory pathology. This work aimed to characterize the nature of the in vivo mucosal immune response to A perfoliata, and to investigate the role of A perfoliata excretory‐secretory components in modulating in vitro immune responses. Real‐time PCR detected elevation of IL13 and TGFβ transcription in early‐stage A perfoliata infection. In late‐stage infection, IL‐13, IL4 and Ifn transcripts were reduced while the regulatory cytokines, TGFβ, IL10 and the transcription factor FOXP3 were increased in tissue close to the site of A perfoliata attachment; indicating downregulation of T‐cell responses to A perfoliata . In vitro, A perfoliata excretory‐secretory products induced apoptosis of the Jurkat T‐cell line and premature cell death of ConA stimulated equine peripheral blood leucocytes. Analysis of cytokine transcription patterns in the leucocyte cultures showed a marked inhibition of IL‐1 and IL‐2 suggesting that a lack of T‐cell growth factor transcription underlies the mechanism of the induced equine T‐cell death. These preliminary findings suggest A perfoliata may have the ability to down‐regulate host T‐cell responses.